Adipokines as Potential Biomarkers in Pregnancy: A Naturalistic Study of Adipokines in Pregnant Women and Newborns - Cristina Mihaela Ormindean; Răzvan Ciortea; Andrei Mihai Măluțan; Carmen Elena Bucuri; Doru Mihai Diculescu; Cristian Ioan Iuhas; Ciprian Gheorghe Porumb; Vlad Ormindean; Maria Patricia Roman; Ionel Daniel Nati; Viorela Suciu; Alexandru Emil Hăprean; et al. (Biomolecules)
Maternal obesity is an escalating public health concern that adversely affects pregnancy outcomes. Adipokines play a key role in regulating metabolism and fetal development, but their dynamic changes during pregnancy remain inadequately understood. Objective: This study investigates maternal and fetal adipokine variations throughout pregnancy and their associations with maternal body mass index (BMI), abdominal wall thickness, and neonatal outcomes. Methods: A prospective case-control study was conducted involving 74 pregnant women categorized by BMI. Maternal blood samples were collected at mid-pregnancy and delivery, and additional analysis of umbilical-cord blood was performed. Clinical parameters such as BMI, abdominal wall thickness, and fetal growth metrics were also recorded. Results: Adiponectin levels were significantly lower in obese pregnancies, whereas leptin and visfatin levels increased with higher maternal BMI. Umbilical-cord blood leptin levels correlated positively with maternal BMI and neonatal birth weight, while ghrelin levels were reduced in neonates born to obese mothers. Significant adipokine fluctuations were observed between mid-pregnancy and delivery. Conclusions: Maternal obesity is associated with distinct alterations in adipokine profiles. These findings highlight the potential of maternal adipokines, given their links to maternal adiposity, as predictive biomarkers for adverse pregnancy outcomes and long-term metabolic risks in offspring. Further interventional research is warranted to evaluate targeted strategies aimed at improving perinatal metabolic health.